Chirality sensing and discrimination of lysine derivatives in water with a dyn[4]arene. Issue 99 (22nd November 2016) - Vial, Laurent; Dumartin, Melissa; Donnier-Maréchal, Marion; Perret, Florent; Francoia, Jean-Patrick; Leclaire, Julien
Abstract : For sensing purposes, we took advantage of the conformational lability of a dyn[4]arene receptor for the generation of induced circular dichroism outputs in the presence of various lysine derivatives. Abstract : The asymmetric deformation of a dyn[4]arene upon the binding of various lysine derivatives leads to distinct induced circular dichroism outputs in buffered water, which can be exploited not only for the determination of their enantiomeric excesses, but also for their classification by linear discriminant analysis.